Heterotrophic Bacterioplankton Growth and Physiological Properties in Red Sea Tropical Shallow Ecosystems With Different Dissolved Organic Matter Sources - Silva, Luis; Calleja, Maria Ll.; Huete-Stauffer, Tamara M.; Ivetic, Snjezana; Ansari, Mohd I.; Viegas, Miguel; Morán, Xosé Anxelu G. (Frontiers in Microbiology, 2022)
Despite the key role of heterotrophic bacterioplankton in the biogeochemistry of tropical coastal waters, their dynamics have been poorly investigated in relation with the different dissolved organic matter (DOM) pools usually available. In this study we conducted 4 seasonal incubations of unfiltered and predator-free seawater (Community and Filtered treatment, respectively) at 3 coastal sites characterized by different dominant DOM sources: Seagrass, Mangrove and Phytoplankton. Bacterial abundance, growth and physiological status were assessed by flow cytometry and community composition by 16S rRNA gene amplicons. The Seagrass site showed the highest initial abundances (6.93 ± 0.30 x 105 cells mL-1), coincident with maximum DOC concentrations (>100 µmol C L-1), while growth rates peaked at the Mangrove site (1.11 ± 0.09 d-1) and were consistently higher in the Filtered treatment. The ratio between the Filtered and Community maximum abundances (a proxy for top-down control by protistan grazers) showed minimum values at the Seagrass site (1.05 ± 0.05). Since the Mangrove and Seagrass sites shared a similar bacterial diversity, the unexpected lack of bacterial response to predators removal at the latter site could be linked to antimicrobial effect of macrophyte exudates. Nitrogen-rich DOM and fluorescent protein-like components were significantly associated with enhanced specific growth rates along the inshore-offshore gradient. Our study confirms the hypotheses that top-down factors control bacterial standing stocks while specific growth rates are bottom-up controlled in representative Red Sea shallow, oligotrophic ecosystems.